2020
DOI: 10.1101/2020.04.10.036533
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural interactions between pandemic SARS-CoV-2 spike glycoprotein and human Furin protease

Abstract: 17The SARS-CoV-2 pandemic is an urgent global public health emergency and 18 warrants investigating molecular and structural studies addressing the dynamics of viral 19 proteins involved in host cell adhesion. The recent comparative genomic studies highlight 20 the insertion of Furin protease site in the SARS-CoV-2 spike glycoprotein alerting possible 21 modification in the viral spike protein and its eventual entry to host cell and presence of Furin 22 site implicated to virulence. Here we structurally show h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“… 57 Vankadari and Naveen in their 2020 preprint studies express furin as a Ca2+ dependent protease, which is highly expressed in lung cystic fibrosis disorder, and it is involved in the cleavage of SARS-CoV-2 viral glycoprotein. 58 The availability of furin-like cleavage at S1/S2 site of viruses, including SARS-CoV-2 contributes to the pathogenesis of the virus. 57 SARS-CoV-2 utilizes furin for the cleavage of S protein at the S1/S2 site.…”
Section: Proteins Involved In Viral Entry Mechanismmentioning
confidence: 99%
“… 57 Vankadari and Naveen in their 2020 preprint studies express furin as a Ca2+ dependent protease, which is highly expressed in lung cystic fibrosis disorder, and it is involved in the cleavage of SARS-CoV-2 viral glycoprotein. 58 The availability of furin-like cleavage at S1/S2 site of viruses, including SARS-CoV-2 contributes to the pathogenesis of the virus. 57 SARS-CoV-2 utilizes furin for the cleavage of S protein at the S1/S2 site.…”
Section: Proteins Involved In Viral Entry Mechanismmentioning
confidence: 99%
“…Coutard et al identified a furinlike cutting site in the SARS-CoV-2-S which is not available in other SARS-like CoVs such as Pangolin, Bat-CoV, and SARS-CoV-1. MERS has a pseudo-furin-binding site (Coutard et al, 2020;Vankadari, 2020). Likewise, Vankadari found that structurally, furin interacts with the SARS-CoV-2-S that highlighted the mechanism of viral host cell entry (Vankadari, 2020).…”
Section: The Functional Role Of Host Proteases In Sars-cov-2 Infectionmentioning
confidence: 97%
“…MERS has a pseudo-furin-binding site (Coutard et al, 2020;Vankadari, 2020). Likewise, Vankadari found that structurally, furin interacts with the SARS-CoV-2-S that highlighted the mechanism of viral host cell entry (Vankadari, 2020).…”
Section: The Functional Role Of Host Proteases In Sars-cov-2 Infectionmentioning
confidence: 97%
“…The spike proteins of SARS-CoV-2 has high affinity to the cellular receptor angiotensin-converting enzyme 2 (ACE2) for their entry inside the cells [4]. The higher binding affinity of SARS-CoV-2 spike protein to the human receptor ACE2 is due to presence of functional polybasic furin cleavage site at the S1-S2 boundary in the spike glycoprotein [5]. Zoonosis is common among CoVs and they can be transmitted from one animal species to another, animals to humans, and humans to humans [6; 7].…”
mentioning
confidence: 99%